2008
DOI: 10.1097/shk.0b013e31811ff509
|View full text |Cite
|
Sign up to set email alerts
|

Epinephrine Versus Dopamine to Treat Shock in Hypoxic Newborn Pigs Resuscitated With 100% Oxygen

Abstract: Shock and tissue hypoperfusion are common after asphyxia. We compared systemic and regional hemodynamic effects of epinephrine and dopamine in the treatment of shock and hypotension in asphyxiated newborn piglets resuscitated with 100% oxygen. Twenty-four piglets (1-3 days old; weight, 1.4-2.6 kg) were acutely instrumented to measure cardiac index (CI), carotid, mesenteric and renal arterial blood flows, and mean systemic (SAPs) and pulmonary arterial pressures (PAPs). Piglets had normocapnic alveolar hypoxia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 32 publications
1
10
1
Order By: Relevance
“…Although dopamine has traditionally been suggested to raise pressure through inotropic effects at low doses and through pressor effects at higher doses (Evans, 2006), the evidence for this is mixed. In short‐term studies in newborn piglets after hypoxia, dopamine typically had little effect on systemic vascular resistance (Barrington et al 1995; Cheung & Barrington, 2001) but increased MAP modestly (Obaid et al 2008; Joynt et al 2010), suggesting a primarily cardiac effect at doses of up to 20 μg kg −1 min −1 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although dopamine has traditionally been suggested to raise pressure through inotropic effects at low doses and through pressor effects at higher doses (Evans, 2006), the evidence for this is mixed. In short‐term studies in newborn piglets after hypoxia, dopamine typically had little effect on systemic vascular resistance (Barrington et al 1995; Cheung & Barrington, 2001) but increased MAP modestly (Obaid et al 2008; Joynt et al 2010), suggesting a primarily cardiac effect at doses of up to 20 μg kg −1 min −1 .…”
Section: Discussionmentioning
confidence: 99%
“…Early clinical studies suggested that low‐dose dopamine (2.5 μg kg −1 min −1 ) was associated with increased contractility and systolic blood pressure in severely asphyxiated neonates (DiSessa et al 1981), with primarily vasopressor actions at higher doses (Seri & Evans, 2001). In newborn piglets exposed to acute hypoxia followed by hyperoxia, infusion of dopamine (and other related inotropic agents, including adrenaline, dobutamine and milrinone) can acutely increase arterial blood pressure and perfusion of key organs for several hours, primarily by increasing cardiac output, consistent with primarily inotropic effects (Barrington et al 1995; Cheung & Barrington, 2001; Obaid et al 2008; Joynt et al 2010). It is unknown whether these benefits are persistent.…”
mentioning
confidence: 99%
“…Other than dopamine, epinephrine is commonly used in neonatal intensive care units. A significant improvement of cardiac function has been observed after administration of epinephrine in various asphyxiated newborn porcine models ( 9 , 10 ). Clinically, epinephrine has been shown as effective as dopamine for the treatment of hypotension in low-birth-weight infants ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its vasoregulatory effect on the cerebral circulation, the effect of CO 2 on myocardial injury following reoxygenation has been shown by Borke et al [13] . Nevertheless, the animals are usually critically ill with the features of clinical asphyxia, such as shock, hypotension and multi-organ dysfunction or failure [14] .…”
Section: Protocol Of Experimental Asphyxia and Reoxygenationmentioning
confidence: 99%